Interactive relations among time, music and emotion - Samartzi, Stavroula; Panagiotidi, Maria (Psychology: the Journal of the Hellenic Psychological Society, 2020)
Research so far has shown that the emotional content of information affects time perception, through the mechanism of subjectivisation (i.e. shrinking or expanding temporal duration as a result of positive and negative emotional valence, respectively). Additionally, preliminary studies suggest that musically trained individuals compared to untrained ones tend to make more accurate duration judgements. Finally, it is known that music can induce specific moods; two of the main factors that determine the relationship between music and emotion are the structural features of the song and the features of the listener. However, it is not clear whether any interactive relations exist among these factors. In this study we attempted to address this particular gap in our current knowledge. As neuroscience studies show, when non musicians are listening to music there is activation of right cerebral areas while musicians show left hemispheric dominance. Right cerebral areas are related to the recognition and the expression of emotions and their activation suggests a cognitive processing based on the emotional valence of songs. Thus, it seems that musical training affects emotion (by inducing certain moods) that, consecutively, affects time estimation.